2020
DOI: 10.3846/jcem.2020.11820
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Harmony Under Multi-Constraint Objectives: The Perspective of Meta-Analysis

Abstract: Harmony is the process of coordinated development between the elements, subsystems and the environment in each Engineering stage of the engineering implementation. Quality, duration, cost and risk are the key factors to achieve engineering harmony. Clarifying the influencing factors of engineering harmony and its mechanism can improve the possibility of success. The meta-analysis method is used to carry out a restudy of existing researches of engineering harmony. First, quality, duration, cost and ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 100 publications
0
5
0
Order By: Relevance
“…Meanwhile, a good natural ecology is embodied in a people-oriented ecological environment. It promotes RH and further promotes the positive role of natural ecology between RH and engineering harmony [13]. Therefore, the hypothesis of H1a is established.…”
Section: The Moderating Effects Of Natural Ecologymentioning
confidence: 93%
See 3 more Smart Citations
“…Meanwhile, a good natural ecology is embodied in a people-oriented ecological environment. It promotes RH and further promotes the positive role of natural ecology between RH and engineering harmony [13]. Therefore, the hypothesis of H1a is established.…”
Section: The Moderating Effects Of Natural Ecologymentioning
confidence: 93%
“…Secondly, as the main objectives of engineering management are quality, duration, cost, and risk, a lot of the literature mainly focuses on the relationship between factors such as quality, duration, cost, safety, and risk and the realization of engineering harmony [2,6,34]. Wang Qiankun used the meta-analysis method to conduct further research on 29 original studies and found that quality, duration, cost, and risk have positive impacts on the realization of engineering harmony [13]. Wyke and Lindhard (2023) used the principal component analysis method to identify potential factors that affect the cost and duration overruns of public construction projects [35].…”
Section: Engineering Construction Harmony and Its Influencing Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, subjective risks are behavioral risks caused by human factors that can be avoided or controlled by people themselves, which now receive more attention [7]. Specifically, stakeholders are the most active productivity factors throughout the engineering projects, and the complexity and uncertainty of their behavior may trigger the occurrence of risk events [9,10]. However, most of the current studies control the occurrence of objective risk events, analyze the probability of the occurrence of risk events and the resulting losses [11], and have not yet conducted systematic research on stakeholder behavioral risks.…”
Section: Introductionmentioning
confidence: 99%